2016
DOI: 10.21511/imfi.13(3-1).2016.11
|View full text |Cite
|
Sign up to set email alerts
|

A holistic view of the use of corporate culture conveyed by internal marketing for enhancing stability, sustainability and consistency in service quality

Abstract: "A holistic view of the use of corporate culture conveyed by internal marketing for enhancing stability, sustainability and consistency in service quality" A holistic view of the use of corporate culture conveyed by internal marketing for enhancing stability, sustainability and consistency in service quality Abstract While businesses worldwide are aiming increasingly on the sustainability in various business areas, customer service is by nature not consistent and stable, because it is delivered by human beings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…This is partly due to the notion that the Organizational Culture which is inculcated into students and employees is strikingly different from that in other service sectors (Ngacha & Onyango, 2017). A wellplanned, well-maintained, positive, consistent and long-term Organizational Culture enhances solid and feasible Service Quality that conforms with organizational goals (Botha, 2016;Jo Ey & Yazdanifard, 2014). The hypothesized relationship was shown in Figure 1.…”
Section: Relationship Between Organizational Culture and Service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is partly due to the notion that the Organizational Culture which is inculcated into students and employees is strikingly different from that in other service sectors (Ngacha & Onyango, 2017). A wellplanned, well-maintained, positive, consistent and long-term Organizational Culture enhances solid and feasible Service Quality that conforms with organizational goals (Botha, 2016;Jo Ey & Yazdanifard, 2014). The hypothesized relationship was shown in Figure 1.…”
Section: Relationship Between Organizational Culture and Service Qualitymentioning
confidence: 99%
“…Since universities are operating in extremely challenging and dynamic environments, attaining excellence and enhancing Service Quality provides a huge competitive advantage thus helping universities to set themselves apart from their competitors (Chong & Ahmed, 2015;Arif, Ilyas, & Hameed, 2013;Mazzarol & Soutar, 2012). A well-planned, well-maintained, positive, consistent and long-term Organizational Culture enhances stable and sustainable Service Quality that is in line with university's business objectives (Botha, 2016;Jo Ey, & Yazdanifard, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature has found that SQ affects OP and is influenced by ITC (Chan and Wang, 2012) and SP (Albort-Morant et al, 2016). Currently, there is consensus that the increasing focus on sustainability is altering the competitive landscape, forcing organizations to adopt robust environmental policies, community, customers, employees and products (Botha, 2016). Thus, technological solutions in the hospitality context can be exploited to improve profitability, productivity and SQ (Khan et al, 2021;Mandi c and Prani cevi c, 2019) to alter the perception of SP.…”
Section: Theoretical Background and Hypotheses Development 21 It Capa...mentioning
confidence: 99%
“…Also, the importance of customer service quality was emphasized by Botha (2016). The author considered the interconnection between corporate culture, customer service and organizational performance.…”
Section: Literature Reviewmentioning
confidence: 99%